PENGUATAN LITERASI KEUANGAN UNTUK PENGELOLAAN DANA MANDIRI RT DI DESA TALES KEDIRI - Dita Riyanto; Angga Rizka Lidiawan; Yuliana Nurul Islami; Budi Heryanto; Wahyu Agung Gumelar (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This service focuses on improving financial literacy as a solution to the low transparency and accountability in fund management at the Neighborhood Association (RT) level in Tales Village, Kediri. The goal is to equip RT 02 RW 05 administrators and residents with a basic understanding and skills in budget planning, financial recording, and accountable reporting. The activities were carried out through a participatory approach and the Asset-Based Community Development (ABCD) method, including training, technical assistance, and participatory discussion forums. The results showed significant changes, such as the formation of a standard bookkeeping system, increased citizen participation in contributions, and the emergence of new local leaders in RT fund management. This program succeeded in building new institutions that support transparency, strengthen citizen trust, and encourage RT independence through more professional and participatory financial management.